1998
DOI: 10.1016/s0304-4076(97)00111-5
|View full text |Cite
|
Sign up to set email alerts
|

Pitfalls in testing for long run relationships

Abstract: This paper analyzes the robustness of the two most commonly used cointegration tests: the single equation based test of Engle and Granger (EG) and the system based test of Johansen. We show analytically and numerically several important situations where the Johansen LR tests tend to find spurious cointegration with probability approaching one asymptotically. The situations investigated are of two types. The first one corresponds to variables that have long-memory properties and a trending behavior, but they ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
96
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 164 publications
(97 citation statements)
references
References 50 publications
(52 reference statements)
1
96
0
Order By: Relevance
“…This issue can have serious consequences for the analysis of the medium and long-run properties of macroeconomic and …nancial variables. For instance, (i) shocks could be identi…ed as permanent when in fact they die out eventually, and (ii) two series could be considered as spuriously cointegrated when they are independent at all leads and lags (see Gonzalo and Lee, 1998). Further, these mistakes are more likely to occur in the presence of deterministic components as, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…This issue can have serious consequences for the analysis of the medium and long-run properties of macroeconomic and …nancial variables. For instance, (i) shocks could be identi…ed as permanent when in fact they die out eventually, and (ii) two series could be considered as spuriously cointegrated when they are independent at all leads and lags (see Gonzalo and Lee, 1998). Further, these mistakes are more likely to occur in the presence of deterministic components as, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…One group of tests looks at the full system of equations in a VAR framework (Johansen's tests, Stock and Watson (1988) SW test, tests on the coefficient of the error correction terms among others) while a second group looks at single equation regressions involving the variables that are potentially cointegrated (Engle and Granger Augmented (Haug (1996), Gonzalo and Lee (1998), Bewley and Yang (1998), Boswijk and Frances (1992), Kremers et al (1992) and Ericsson and Mackinnon (1999) …”
Section: Introductionmentioning
confidence: 99%
“…As remarked by Gonzalo and Lee (1998), when breaks are present in mean or/and trend spurious cointegration may occur. Likewise, Noh and Kim (2003) indicated that if breaks occur in the variance of innovation errors of two independent time series, especially in early periods, spurious cointegration can appear.…”
Section: Maki (2012) Cointegration Analysismentioning
confidence: 90%